Biomedical contributions to laboratory and imaging care for autistic people from the perspective of humanized medicine (Research, Society and Development, 2024)
The humanized approach to biomedicine emphasizes the well-being and dignity of individuals with autism, taking into account their specific needs and singularities. This study aims to promote the elucidation of possible approaches for managing autistic patients during laboratory and imaging exams, with the purpose of improving their skills and abilities, among biomedical professionals. The methodology used consists of a qualitative research approach, using a bibliographic and descriptive review. Sixteen articles were included, which constituted the reference basis and the core for the elaboration of the protocols to be followed for performing laboratory and imaging exams. It was concluded that, considering the particularities of autistic patients, humanization in care becomes indispensable, as well as the execution of the protocol steps, since this corresponds to a sequence of appropriate strategies for managing these patients, reducing discomfort and anxiety in laboratory and imaging exams, highlighting the role of the biomedical professional in the development and execution of these practices, being responsible for the collection of biological materials and conducting imaging exams.